2019
DOI: 10.3390/ijerph16214171
|View full text |Cite
|
Sign up to set email alerts
|

Food Security and Obesity among Mexican Agricultural Migrant Workers

Abstract: Mexican migrant farm workers are one of the poorest and most marginalized social groups within the country. They face the double burden of malnutrition, food insecurity, as well as harsh living and labor conditions. Objective: To examine the relationship between household food insecurity (HFI) and obesity in a population of migrant farm workers in highly modernized agribusiness areas of Northwest Mexico. Methods: This was a cross-sectional study with a concentric (site) (n = 146 households) and systematic sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 27 publications
1
14
0
1
Order By: Relevance
“…A cross-sectional study among 250 participants in Dutch disadvantaged neighborhoods found that food insecurity was associated with obesity in models adjusted for demographics, socioeconomic indicators, and lifestyle factors (OR = 2.51, 95% CI 0.98, 6.48), but not with overweight (OR = 1.15, 95% CI 0.46, 2.85) [ 12 ]. Likewise, a study of 146 households agricultural migrant workers in Mexico found that household food insecurity was associated with greater odds of obesity overall (OR = 5.18, 95% Cl 1.37, 19.6), but that the association varied significantly by gender such that risk was greater for women than men [ 13 ]. A similar study among 828 low-income immigrants in Boston, MA, showed that, in adjusted models, participants reporting food hardship were 17% more likely to be obese than those who did not report food hardship (RR 1.17, 95% CI 1.07, 1.29) [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…A cross-sectional study among 250 participants in Dutch disadvantaged neighborhoods found that food insecurity was associated with obesity in models adjusted for demographics, socioeconomic indicators, and lifestyle factors (OR = 2.51, 95% CI 0.98, 6.48), but not with overweight (OR = 1.15, 95% CI 0.46, 2.85) [ 12 ]. Likewise, a study of 146 households agricultural migrant workers in Mexico found that household food insecurity was associated with greater odds of obesity overall (OR = 5.18, 95% Cl 1.37, 19.6), but that the association varied significantly by gender such that risk was greater for women than men [ 13 ]. A similar study among 828 low-income immigrants in Boston, MA, showed that, in adjusted models, participants reporting food hardship were 17% more likely to be obese than those who did not report food hardship (RR 1.17, 95% CI 1.07, 1.29) [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…An additional 23.6 percent of indigenous Mexicans are socially vulnerable and economically precarious (CONEVAL, 2019). The challenges of rural poverty include limited incomes, limited access to education and health care services as well as high levels of food insecurity (Castañeda et al, 2019;Juarez & Gonzalez, 2010;Magaña-Lemus et al, 2016;Villarreal, 2014).…”
Section: Indigenous Povertymentioning
confidence: 99%
“…The lesson that can we learn from Castañeda's study [8], meanwhile, is that the presence of large migrant communities-often also ethnically distinct from the resident population in terms of life habits-that have formed across certain more attractive areas commits the attention of public health to changes in lifestyle habits (e.g., eating habits, the consumption of alcohol and tobacco, etc.) and health promotion in these specific populations.…”
Section: Forewordmentioning
confidence: 99%
“…In a nutshell, the route towards the full addressing of the demand for migrants' and refugees' healthcare is long and arduous, but this Special Issue shows small but good progress and provides some starting points for discussion and strategies for addressing the emerging challenges [4,5,[7][8][9][10][11]. We, as guest editors, hope that this Special Issue may serve as a stimulus for those who are interested in or involved with the discussion of challenges, opportunities, and solutions to overcome boundaries that affect the healthcare of migrants and refugees.…”
Section: Forewordmentioning
confidence: 99%